Visual neuroprosthesis: present and future perspectives - Lešták, Ján; Chod, Jiří; Rosina, Jozef; Hána, Karel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2022)
The purpose of this study is to provide an overview of the replacements used in lost vision in the form of the bionic eye, to show their deficiencies and outline other possibilities for non-invasive stimulation of functional areas of the visual cortex. The review highlights the damage not only to the primary altered cellular structures, but also to all other horizontally and vertically localised structures. Based on the results of a large number of functional magnetic resonance imaging and electrophysiological methods, the authors focus on the pathology of the entire visual pathway in pigmentary retinopathy (PR) and age-related macular degeneration (AMD). This study provides a recent overview of the possible systems used to replace lost vision. These range from stimulation with intraocular implants, through stimulation of the optic nerve and lateral geniculate nucleus to the visual cortex. The second part deals with the design of image processing technology and its transformation into the form of transcranial stimulation of undamaged parts of the brain, which is protected by a patent. This is comprehensive overview of the current possibilities of replacement of lost vision and a proposal for a new non-invasive methods of stimulation of functional neurons of the visual cortex.
Keywords: zrakové korové centrum; Electric Stimulation Therapy; Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; Humans; Optic Nerve; Visual Cortex; lidé; elektrostimulační terapie; Brain; nervus opticus